Dziedzictwo kulturowe świętej Kingi. Ze zbiorów Biblioteki Sióstr Klarysek w Starym Sączu - Mirek, Małgorzata (Archiwa, Biblioteki i Muzea Kościelne, 2017)
From 14 June to 25 August 2013, the “Dawna Synagoga” Gallery, one of the branches of the District Museum in Nowy Sącz, hosted the exhibition "St Kinga’s Cultural Heritage". The purpose of this exhibition was to show a wider audience the artistic heritage of the Poor Clares Monastery in Stary Sącz. Most of the exhibits were presented outside the monastery walls for the first time. Among them were items belonging to St Kinga, valuable works of handicraft, the oldest written texts, as well as sculptures and paintings of high artistic value from the 15th to the 18th centuries.